2013
DOI: 10.1186/1471-2334-13-500
|View full text |Cite
|
Sign up to set email alerts
|

The impact of inappropriate antibiotics on bacteremia patients in a community hospital in Taiwan: an emphasis on the impact of referral information for cases from a hospital affiliated nursing home

Abstract: BackgroundEvidence for the impact of inappropriate antimicrobial therapy on bacteremia is mainly from studies in medical centers. We investigated the impact of inappropriate antimicrobial therapy on bacteremia in a community hospital. In particular, patients from the hospital’s affiliated nursing home were sent to the hospital with adequate referral information.MethodsWe performed a retrospective study to collect data of patients with bacteremia in a community hospital in Taiwan from 2005 to 2007.ResultsA tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…The findings of this study 7 were consistent with studies in the 2005 review 1 and will not be discussed further. The literature review identified 6 studies published since 2005 that met the inclusion criteria [8][9][10][11][12][13] : 2 studies evaluated exclusively NHABSI 8,9 and 4 studies compared NHABSI to community-or hospital-associated BSI. [10][11][12][13] Studies that evaluated exclusively NHABSI Table 1 summarizes the characteristics and findings of the 2 studies in which only NHABSI was evaluated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings of this study 7 were consistent with studies in the 2005 review 1 and will not be discussed further. The literature review identified 6 studies published since 2005 that met the inclusion criteria [8][9][10][11][12][13] : 2 studies evaluated exclusively NHABSI 8,9 and 4 studies compared NHABSI to community-or hospital-associated BSI. [10][11][12][13] Studies that evaluated exclusively NHABSI Table 1 summarizes the characteristics and findings of the 2 studies in which only NHABSI was evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…The literature review identified 6 studies published since 2005 that met the inclusion criteria [8][9][10][11][12][13] : 2 studies evaluated exclusively NHABSI 8,9 and 4 studies compared NHABSI to community-or hospital-associated BSI. [10][11][12][13] Studies that evaluated exclusively NHABSI Table 1 summarizes the characteristics and findings of the 2 studies in which only NHABSI was evaluated. The study by Almog et al 8 was a letter to the editor and was included in this review because it evaluated a large number of cases of NHABSI (N = 177) and provided information on antibiotic resistance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yang et al [22] reported that initial inappropriate antibiotic administration or delayed appropriate antibiotic administration were significantly associated with higher mortality rates in patients with BSI. However, while starting antimicrobial treatment for BSI in transplant patients, a dilemma frequently occurs whether or not to initiate immediate therapy targeted to the suspected infecting agent, in a situation when results from conventional identification methods are available only 24 to 48 h after a positive signal.…”
Section: Discussionmentioning
confidence: 98%
“…Having specific data about the prevalence of antibiotic resistance among common pathogens in patients arriving from nursing homes and the community can improve the specificity and efficacy of initial antibiotic therapy. Such an approach could notably reduce mortality in patients with bacteraemia (Artero et al, 2010; Yang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%